COMMUNICATION STRATEGY OF THE REGIONAL LEADERSHIP OF THE MUHAMMADIYAH STUDENT ASSOCIATION OF LAMPUNG - Ahmad Fiqri Baihaqi; Purwanto Putra (Adisam Publisher, 2026)
Rapid developments in the era of globalisation mean that effective communication, both internally and externally, is a very important factor for the success of Islamic organisations in achieving their organisational goals. Communication plays a very significant role in ensuring that all organisational activities continue to run smoothly. In the context of organisations, communication is one of the functions that allows people to get to know each other's personalities, including leaders and members who have different needs. This study aims to improve organisational communication skills at PW IPM Lampung. The research method used is qualitative research with a descriptive approach. Data collection techniques used interviews, observation and documentation. The results of the study show that the leadership's strategy in improving the communication skills of PW IPM Lampung members is in line with the concept of communication. Through the application of this strategic concept, the leadership is able to foster effective relationships between members of the organisation, improve coordination, and provide direction and evaluation to achieve the goals and work programmes of the organisation.